The cell-intrinsic requirement of Sox6 for cortical interneuron development. - Wegner, Michael; et al. (Neuron, 2009)
We describe the role of Sox6 in cortical interneuron development, from a cellular to a behavioral level. We identify Sox6 as a protein expressed continuously within MGE-derived cortical interneurons from postmitotic progenitor stages into adulthood. Both its expression pattern and null phenotype suggests that Sox6 gene function is closely linked to that of Lhx6. In both Lhx6 and Sox6 null animals, the expression of PV and SST and the position of both basket and Martinotti neurons are abnormal. We find that Sox6 functions downstream of Lhx6. Electrophysiological analysis of Sox6 mutant cortical interneurons revealed that basket cells, even when mispositioned, retain characteristic but immature fast-spiking physiological features. Our data suggest that Sox6 is not required for the specification of MGE-derived cortical interneurons. It is, however, necessary for their normal positioning and maturation. As a consequence, the specific removal of Sox6 from this population results in a severe epileptic encephalopathy. © 2009 Elsevier Inc. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2009.med.IB.LPCIPDBI.thecel
Keywords: DEVBIO; MOLNEURO